The Fragmentation of Yugoslavia : Nationalism and War in the Balkans - Pavković, Aleksandar (New York St. Martin's Press, 2000)
Yugoslavia was created by World War I. From 1991, a series of wars broke Yugoslavia into new and smaller states. The victors presented these as wars of national liberation. This work traces the origins of ideologies, and outlines their use in the creation of new states and new political regimes.
Include Map, Note, References and Index
Keywords: Yugoslavia -- Nationalism -- Yugoslav War (1991-1995) -- Diplomatic history